Beginning PHP and Oracle from novice to professional - Gilmore; Bryla (Berkeley, CA Apress, 2007)
Provides instructions on building applications and Web sites using the PHP language along with the Oracle database
"Learn how to build dynamic, database-driven web sites with the popular PHP language and powerful Oracle database"--Cover
Keywords: Database management; Open source software; PHP (Computer program language); Relational databases; Web site development